ESTIMATION OF THE POPULATION EXPOSURE DOSES FROM NATURAL AND ARTIFICIAL RADIONUCLIDES DUE TO DRINKING-WATER CONSUMPTION FOR THE INHABITANTS OF DIFFERENT AREAS OF RUSSIAN FEDERATION - Ju. N. Goncharova; L. N. Basalaeva; M. V. Kaduka; N. S. Shvydko; A. N. Kaduka (Радиационная гигиена)
The report contains data on specific activity values of natural and artificial radionuclides in the water of underground and surface sources in 19 areas of Russian Federation and data on population internal exposure doses from drinking water consumption in these areas.